Pedagogical Strategies and ICT Practices of English Language Teachers in Nepali Schools - Phunyal , Balkrishna (GS Spark: Journal of Applied Academic Discourse, 2025)
This study explores the perceptions and classroom practices of English language teachers in Nepali schools, focusing on their pedagogical approaches, use of Information and Communication Technology (ICT), and the challenges they face. Despite the critical role of English in Nepal’s education and social mobility, teachers often struggle to align their positive attitudes toward modern, student cantered methods with actual classroom practices due to systemic constraints. The research highlights a shift toward communicative and task-based teaching, yet traditional methods persist due to large class sizes, exam-driven curricula, and limited resources. ICT integration, though viewed favorably, is hindered by infrastructural issues like poor internet access and insufficient training. The study also examines the impact of Nepal’s multilingual context on teaching practices and the emerging trend of reflective teaching and participatory action research. Findings underscore the need for targeted professional development, equitable resource distribution, and policy reforms to bridge the gap between teachers’ aspirations and classroom realities, fostering more effective English language education in Nepal.